Market Repositioning Strategies of a Real Estate Business - Marilao, Anna Rose (International Journal of Sustainability and Advanced Integrated Research, 2026)
The Philippine real estate industry has become increasingly competitive due to rapid digital transformation, changing consumer preferences, and the growing demand for affordable housing. This study examined the market repositioning strategies of Company A, a mid-sized real estate developer, to strengthen its competitive advantage and achieve sustainable growth. Specifically, the study assessed the company's current market position, identified internal strengths and weaknesses, analyzed industry opportunities and threats through benchmarking and environmental scanning, and developed strategic recommendations for market repositioning.A descriptive case study approach was employed using qualitative and quantitative data gathered from company financial records, sales reports, industry benchmarks, and strategic management tools, including SWOT, PESTEL, and competitor analyses. The findings revealed that Company A demonstrates strengths in customer-centered service, affordability, and consistent revenue growth. However, the company continues to face challenges related to limited digital adoption, weak brand differentiation, operational inefficiencies, fluctuating profitability, and restricted market penetration. Benchmarking further indicated that industry leaders maintain competitive advantages through advanced customer relationship management (CRM) systems, digital marketing capabilities, broader geographic presence, and enhanced customer engagement.Based on the findings, the study proposes an integrated market repositioning strategy focusing on CRM implementation, digital-first marketing, strategic brand renewal, and innovative financing programs to improve customer experience and sales performance. These initiatives are expected to strengthen brand visibility, enhance operational efficiency, increase customer satisfaction, and improve long-term competitiveness. The study contributes to strategic management and real estate literature by providing a practical framework for market repositioning that can assist real estate developers in adapting to the evolving demands of the Philippine housing market.
Keywords: Market Repositioning, Real Estate, Affordable Housing, Competitive Strategy, Digital Transformation, Customer Relationship Management, Brand Positioning, Philippines